(untitled) (Economic studies journal, 2025)
Abstract This study aims to shed light on the importance of applying accounting cybersecurity in Libyan commercial banks operating in the city of Sirte. To achieve the objectives of the study, the descriptive analytical approach was adopted, where the questionnaire was used as the main tool for collecting data, while ensuring its validity and reliability. The data were also analyzed using the (SPSS) program by applying descriptive and inferential statistical methods. The results of the study showed that employees of commercial banks in the city of Sirte believe that their banks are aware of and conscious of the importance of applying accounting cybersecurity. The results also indicated that there are major challenges and obstacles facing these banks in applying accounting cybersecurity. In addition, the results confirmed that there is great interest by the Central Bank and commercial banks in the city of Sirte in enhancing accounting cybersecurity, as this interest focuses on vital aspects such as: protecting sensitive financial data, enhancing trust and credibility, reducing risks, and ensuring compliance with security standards. Finally, the study presented a set of recommendations, the most important of which are: training courses and workshops should be organized for bank employees to enhance their awareness of the latest cyber threats and best security practices. It is also necessary to invest in advanced cybersecurity technologies and continuously update systems to keep pace with technological developments and new risks. In addition, it is necessary to enhance cooperation with the Central Bank and government agencies to exchange information and expertise in the field of cybersecurity, which supports joint efforts in this field.